Penerapan Metode Theory Of Planned Behavior (TPB) dan Technology Acceptance Model (TAM) Pada Pengguna SIAKAD - Muh. Nurtanzis Sutoyo; Qammaddin Qammaddin (Unversitas Muhammadiyah Mataram, 2023)
Abstract: The Academic Information System has become an integral part of modern educational institutions, aiming to enhance efficiency, accuracy, and accessibility in managing academic information. The adoption and usage of the Academic Information System (often referred to by its local abbreviation, SIAKAD) are often influenced by the psychological and behavioral factors of its users. To understand and address these challenges, the TPB (Theory of Planned Behavior) and TAM (Technology Acceptance Model) methodologies are applied to determine the behavior and acceptance levels of SIAKAD. The nature of this research is quantitative. The sampling technique is random sampling, taken from 30 Study Programs with a total of 89 respondents. Research data were obtained from the results of the respondent's questionnaire. The data was then analyzed using the Partial Least Square (PLS) approach. The findings show that the variable of ease of application use has a significant influence. This is based on the calculation results that show a T-statistic value of 58.715 (> 1.96). Abstrak: Sistem Informasi Akademik telah menjadi bagian integral dari institusi pendidikan modern, yang bertujuan untuk meningkatkan efisiensi, akurasi, dan aksesibilitas dalam pengelolaan informasi akademik. Penerimaan dan penggunaan SIAKAD seringkali dipengaruhi oleh faktor-faktor psikologis dan perilaku penggunanya. Untuk memahami dan mengatasi tantangan ini, penerapan metode TPB dan TAM digunakan untuk mengetahui tingkat perilaku dan penerimaan SIAKAD. Jenis penelitian pada penelitian ini adalah penelitian kuantitatif. Teknik pengambilan sampel, yaitu random sampling yang diambil dari 30 Program Studi dengan jumlah responden sebanyak 89 orang responden. Data penelitian diperoleh dari hasil kuesioner responden. Kemudian data dianalisis menggunakan pendekatan Partial Least Square (PLS). Hasil penelitian menunjukan bahwa varibel kemudahan menggunakan aplikasi memiliki pengaruh yang cukup besar. Hal ini berdasarkan hasil perhitungan yang menunjukkan T-statistic sebesar 58, 715 (> 1,96).